The Nexus between spatiotemporal land use/land cover dynamics and ecosystem service values in the wabe river catchment, Omo Gibe River Basin, Ethiopia - Yonas Mathewos; Brook Abate; Mulugeta Dadi; Markos Mathewos (Environmental Challenges)
Changes in land use/land cover (LULC) have emerged as a critical concern, impeding sustainable development and affecting natural ecosystems and their services. To address these challenges, a study investigated the linkage between the spatiotemporal dynamics of LULC changes and ecosystem service values (ESVs) from 1986 to 2022 and projected scenarios for 2041 and 2058 in the Wabe River catchment. Historical Landsat imagery was classified under supervised techniques employing maximum likelihood algorithms in ERDAS Imagine; future changes were forecasted using multilayer perceptron neural network and cellular automata-Markov chain algorithms, and the value transfer valuation technique in conjunction with ArcGIS 10.8 was utilized to quantify the nexus between LULC changes and resulting ESVs. The findings revealed notable increases in built-up areas (576.49%) and agriculture (114.62%) alongside declines in grassland (36.46%), forest (22.45%), and agroforestry (22.48%) from 1986 to 2022. Future projections suggest further expansion of built-up areas (55.80%) and agricultural land (15.72%), with corresponding declines in woodland, forest, and agroforestry. ESVs experienced a substantial decline of US$3227.20 million between 1986 and 2022, and are projected to witness a total decrease of US$1410.52 million from 2022 to 2058, driven by changing LULC dynamics, notably affecting high-value ecosystem providers like agroforestry and forests. The trend of ESVs in different agroecological zones varied, with the lowlands showing an increase, while the midlands and highlands experienced consistent decreases. The study underscores the urgent need for collaborative environmental stewardship, advocating sustainable practices and conservation efforts to reverse the declining trend of ESVs and ensure long-term ecosystem resilience.